Morphometric Study of African Spurred Tortoise (Centrochelys sulcata) Based on Age Group - Siagian, Tetty Barunawati; Prayogo, Muhammad Firman Bayu; Widigdaya, Danuja; Pungki, Pungki (Universitas Labuhanbatu, 2023)
Centrochelys sulcata are kept and bred to prevent extinction. The sulkata tortoises were identified to determine their respective identities by measuring them morphometrically. Morphometric studies on sulkata tortoises are still minimal, so a morphometric study of the sulkata tortoises is needed. The purpose of this study was to identify and describe the morphometry of sulcata tortoises with three different age ranges kept in ex-situ conservation. The research sample used 15 sulcata turtles which were divided into 3 groups namely group A (1 year), Group B (2 years), and Group C (3 years). The morphometric parameters measured were body weight, head, carapace, plastron, forelimb, hindlimb and bridge. The results showed that the average body weight of group A, B and C turtles was 2,179 kg, 1,289 kg and 0,167 kg respectively. The average maximum carapace length in a row for groups A, B, C, namely 11.64, 23.18 and 16.72 cm. The average plastron lengths for groups A, B, C were 9.08, 6.44 and 9.24 cm respectively. The average forelimb length in groups A, B and C were 3.04, 6.28 and 7.78 cm respectively. The average hindlimb length for groups A, B, and C were 1.86, 3.5 and 4.04 cm, respectively. The average bridge width for groups A, B and C were 4.36, 8.94 and 10.1 cm respectively. Based on the results of morphometric measurements of the three groups of sulcata tortoises, it was shown that group C had a larger morphometric size than groups B and A, this was due to differences in age and growth factors. Sulcata tortoises group C is 3 years old and belongs to the juvenile group. Sulcata tortoise groups A and B aged 1 and 2 years are included in the yearly group